Research advance and application prospect of therapeutic strategies for Duchenne muscular dystrophy - Cheng ZHANG; Huan LI (Chinese Journal of Contemporary Neurology and Neurosurgery, 2018)
Duchenne muscular dystrophy (DMD) is an X-linked, severe genetic muscular disorder caused by the deficiency of DMD gene. There is still no curative therapy for the disease, but improving survival and life quality of the patients have been achieved due to multidisciplinary interventions. The therapies available for clinical treatment include drug therapies [glucocorticoids, angiotensin converting enzyme inhibitor (ACEI), idebenone, albuterol], management of respiratory system, expecially the use of non-invasive ventilator, rehabilitation therapy focusing on hydrotherapy and prevention of joint contracture, nutritional management, and so on. Advancing therapeutic strategies including gene therapies (exon skipping, nonsense mutation readthrough therapy and adeno-associated virus (AAV) mediated micro/mini-dystrophin therapy), myostatin and compensatory upregulation of utrophin, and gene editing have made great progress in preclinical study and some of them like exon skipping therapy of exon 51 and nonsense mutation readthrough therapy have been studied in a few clinical trials and made some achievements.